The influence of parenting parents on the personal hygiene independence of students with disabilities - Juliana, Tya; Barida, Muya (COUNS-EDU: The International Journal of Counseling and Education, 2020)
Independence of children's personal hygiene is influenced by parenting parents. This study aims to determine the effect of parenting parents on the personal hygiene independence of children with special needs in SLB / G-AB Helen Keller Indonesia. This type of research is quantitative with descriptive correlational research design. Respondents in this study were parents and students. The sampling technique uses saturated samples. Data analysis uses regression analysis. Based on the results of the study note that for 0.004 (0.004 <0.05) the value of the influence of authoritarian parenting, the value of the influence of democratic parenting is 0.029 (0.029 <0.05) and 0.032 (0.032 <0.05) the value of permissive parenting. Based on the explanation above, it can be concluded that the type that most influences children's personal hygiene independence is authoritarian parenting has the most significant and positive influence on the personal hygiene independence of children with special needs in SLB / G-AB Helen Keller Indonesia.